Green Innovations: Artificial Intelligence and Sustainable Materials in Production - Shahrukh Khan Lodhi; Ahmad Yousaf Gill; Hafiz Khawar Hussain (CV. Multi Kreasi Media, 2024)
This study examines the revolutionary potential of integrating artificial intelligence (AI) with sustainable materials in production through a series of case studies, featuring innovations by Adidas, Tesla, Unilever, and IKEA. These illustrations demonstrate how AI may be used to create recyclable goods, maximize material efficiency, and simplify supply chains—all of which greatly lessen the manufacturing process's negative environmental effects. The study also identifies the main domains in which these technologies are propelling improvements in operational effectiveness and environmental sustainability. Robust regulatory frameworks are required to assure the safe, transparent, and equitable implementation of AI as it becomes increasingly integrated into industrial processes. The article also highlights the need for responsible innovation by discussing the ethical and policy ramifications of utilizing AI in sustainable manufacturing, as well as the societal impact of AI on data privacy and the workforce. Lastly, the environmental effects of AI itself are discussed, emphasizing the need for renewable energy sources and energy-efficient AI systems. Through collaboration between governmental, industrial, and social sectors, artificial intelligence (AI) can be leveraged to propel environmentally and socially responsible production methods. In order to create a more sustainable and prosperous future, the paper's conclusion emphasizes the need for a balanced strategy that optimizes AI's benefits while guaranteeing moral and egalitarian outcomes. Going ahead, the report makes the case that artificial intelligence and sustainable materials will play a pivotal role in molding a manufacturing landscape that is both efficient and environmentally beneficial. However, achieving this potential will necessitate managing the dangers and difficulties that come with it carefully.